Adolescents’ daily social media use and mood during the COVID-19 lockdown period - Melissa J. Dreier; Simone Imani Boyd; Saskia L. Jorgensen; Ritika Merai; Jennifer Fedor; Krina C. Durica; Carissa A. Low; Jessica L. Hamilton (Current Research in Ecological and Social Psychology)
Adolescents’ relationship to social media (SM) use shifted significantly during the COVID-19 lockdown. However, less is known about how adolescents’ social media use behaviors and mood were associated during this time. This study examined objective (passively sensed) SM use—including ‘screen time’ (duration of use) and checking (frequency of opening apps), retrospective daily reports of positive and negative affect during SM use, and general negative mood among adolescents during the COVID-19 lockdown period. Participants included 19 adolescents (Mean age = 15.8; 37 % female). Bayesian multilevel models examined whether within person-changes in SM ‘screen time’ and checking were associated with 1) retrospectively reported positive and negative affect while using SM and daily duration of SM use, 2) daily reports of overall negative mood. These relationships were examined both within the same day and prospectively (one day's SM behaviors predicting next-day mood and vise versa). On the same day, stronger positive or negative mood during SM use were associated with more SM ‘screen time’ (duration) and checking. Prospectively (next-day models), checking SM more frequently than usual was uniquely associated with within-person increases in adolescents’ positive mood when using SM the next day (p < .05), but not negative mood when using SM the next day. However, neither ‘screen time’ nor checking were associated with general negative mood on the same day or next day. These findings support the notion that SM is rewarding by highlighting that higher-than-usual SM checking is associated with within-person increases in positive mood during use. These findings also add to growing evidence that social media may not be directly tied to adolescents’ general mood state.